Multiple retained intraocular glass foreign body with late-onset retinal detachment - Prabhushanker Mahalingam; Tasneem Topiwalla; Geetha Ganesan (Journal of Clinical Ophthalmology and Research, 2019)
Successful management of intraocular foreign body (IOFB) is deemed possible by the advent of superior surgical procedures, even in those patients who present late. We report a case of a 46-year-old male, who presented with sudden onset of defective vision in his right eye of 2 days duration and with a previous history of trauma following bulb blast at the age of 5 years. Examination revealed retinal detachment with multiple intraocular glass foreign body in his right eye. The primary management, in this case, was phaco-aspiration of lens through limbal tunnel, scleral buckling, 23G pars plana vitrectomy, IOFB removal through anterior segment, endolaser, and silicone oil injection. After 6 months, silicone oil was removed, and posterior chamber intraocular lens was implanted. This is a rare case wherein multiple glass IOFBs had remained quiescent in the eye for more than four decades resulting in retinal detachment at a later date and successful management with good visual outcome was possible.